EFL Teachers’ Problems in Implementing the Competency-Based Approach in Teaching Writing “The case of EFL Secondary School Teachers in Biskra” - CHELLI, Saliha; KHOUNI, Warda (Sciences humaines, 2014)
In spite of the implementation of the competency-based approach in teaching in the Algerian school, middle and secondary school teachers find it difficult to teach according to this approach. This article aimed to investigate and analyze the main problems encountered by EFL secondary school teachers in teaching writing. What are the main problems encountered by them? To answer this question, we hypothesized that their main difficulties involve lack of theoretical background on the competency-based approach in addition to lack of in-service training. To test this hypothesis, a questionnaire was administered to ten secondary teachers in Biskra. This tool was supplemented by a semi-structured interview with three participants. The results of this research reveal that most of the participants rely on traditional methods mainly because they lack theoretical backgrounds concerning the competency-based approach and training in teaching writing and the other skills under this approach, which requires a new conceptualization in teaching. As a pedagogical application, we suggest the process- genre approach to be used in order to develop students’ writing.